Arbeidskravsprofil, melkesyrekonsentrasjon i blod og opplevd anstrengelser under VM i 1998 og 1999 i gresk-romersk bryting - Tveit, P.; Csergoe, S.; Nilsson, J.; Refsnes, P. E. (2000)
The aim of this study was to examine work-time profiles, blood lactate concentrations and perceived exertion among Greco-Roman wrestlers in the 1998 World Championship. Forty-two senior wrestlers from nine nations were studied in 94 matches. Each match was recorded with a video camera (Panasonic AG 455, film rate: 25 Hz) and analysed for duration of work (wrestling) and rest (interrupt) periods. Blood lactate concentration was determined with an electrochemical device (Analox P-LM5) and a rating of perceived exertion scale (Borg) was used to estimate general exertion and exertion in the extremity and trunk muscles. The mean duration of the matches was 427 s (range 324-535 s), with mean durations of work and rest of 317 and 110 s, respectively. The mean periods of work and rest were 37.2 and 13.8 s, respectively. Mean blood lactate concentration was 14.8 mmol x 1(-1) (range 6.9-20.6). The difference in mean blood lactate concentration between the first- and final-round matches was not significant (P > 0.05). Blood lactate concentration was significantly higher (P < 0.04) in matches of long duration than in those of short duration. The mean general rating of perceived exertion for all matches was 13.8 according to the scale used. Most of the wrestlers (53.3%) perceived exertion to be highest in the flexors of the forearm, followed by the deltoids (17.4%) and the biceps brachii muscles (12.0%). In addition to a relatively high rating of perceived exertion in the arm muscles, this indicates a high specific load on the flexor muscles of the forearm.